Silane-crosslinked resin molded body and its manufacturing method, silane-crosslinkable resin composition and its manufacturing method, and product
Patent Information
- Application Number
- JP2021056251
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0010】 本発明によれば、極低温環境における低温柔軟性と常温での取り扱い性とに優れたシラン架橋樹脂成形体の製造方法、この製造方法により得られるシラン架橋樹脂成形体、及びこの成形体を用いた製品を提供できる。また、このような優れた特性を示すシラン架橋樹脂成形体の製造に好適な、シラン架橋性樹脂組成物及びその製造方法を提供できる。
Smart Images

Figure 0007640329000001 
Figure 0007640329000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a silane-crosslinked resin molded article and a method for producing the same, a silane-crosslinkable resin composition and a method for producing the same, and a product. [Background technology]
[0002] 2. Description of the Related Art Various characteristics are required for wiring materials such as insulated wires, cables, cords, optical fiber cores, and optical fiber cords used for internal wiring or external wiring in electric and electronic devices.
[0003] Wiring materials are used in a variety of environments, and may be used in low-temperature environments such as cold regions, refrigeration facilities, and freezing facilities. From the viewpoint of safety and reliability of the wiring material, wiring materials used in low-temperature environments are required to have low-temperature flexibility so that they can be bent and used without damaging the coating even in low-temperature environments. Patent Documents 1 and 2 disclose methods for manufacturing wiring materials that exhibit flexibility even in low-temperature environments of 0°C or -40°C. Meanwhile, Patent Documents 3 and 4 disclose methods for manufacturing wiring materials that exhibit flexibility at room temperature, although they are not particularly suited to low-temperature environments. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-195575 A [Patent Document 2] JP 2019-008888 A [Patent Document 3] International Publication No. 2015 / 046476 [Patent Document 4] JP 2017-179235 A Summary of the Invention [Problem to be solved by the invention]
[0005] The temperature inside a freezing facility varies depending on the application, and some facilities are used in cryogenic environments, for example, at temperatures below -60° C. All of the wiring materials obtained by the manufacturing methods described in Patent Documents 1, 2, and 4 have a problem in that they cannot maintain their flexibility in a cryogenic environment. On the other hand, even wiring materials used in the above-mentioned cryogenic environments are often installed in room temperature environments, and ease of handling of the wiring materials during installation, for example, low tackiness (adhesion between wiring materials), is also an important factor. If the tackiness is too strong, wiring materials will stick to each other when they are brought into contact with each other, and when the wiring materials are separated, the coating of the wiring material may deform, resulting in a poor appearance. The wiring material obtained by the manufacturing method described in Patent Document 3 was not able to achieve both low-temperature flexibility and ease of handling. Furthermore, wiring materials and the like are required to be crosslinked depending on their applications. For example, insulated electric wires and the like coated with a crosslinked polyethylene mixture as stipulated in the Electrical Appliance and Material Safety Law, the coating is required to be a crosslinked material. The manufacturing method described in Patent Document 2 does not include a crosslinking step.
[0006] An object of the present invention is to provide a method for producing a silane-crosslinked resin molded product that has excellent low-temperature flexibility in an extremely low-temperature environment and excellent handleability at room temperature when used as wiring material, etc., a silane-crosslinked resin molded product obtained by this production method, and a product using the same. Another object of the present invention is to provide a silane-crosslinkable resin composition suitable for producing the silane-crosslinked resin molded article, and a method for producing the same. [Means for solving the problem]
[0007] In the silane crosslinking method, the inventors used a base resin having a density of 0.890 g / cm 3It has been found that by selecting a polyolefin resin having a low glass transition temperature of less than 100° C., and then making the polyolefin resin contain two types of polyolefin resins having different glass transition temperatures (a polyolefin resin having a glass transition temperature of less than -50° C. and a polyolefin resin having a glass transition temperature of more than -50° C. and less than -40° C.), and using a base resin containing these in combination with a styrene elastomer and a mineral oil in specific amounts, and by using specific amounts of an inorganic filler and a component having a melting point of 250° C. or more, a silane crosslinked resin molded body can be produced, and the obtained resin molded body can realize improved low-temperature flexibility in an extremely low-temperature environment and improved handleability at room temperature. Based on these findings, the present inventors have conducted further research and have come up with the present invention.
[0008] That is, the object of the present invention has been achieved by the following means. [1] A method for producing a silane-crosslinked resin molded product, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base resin, and a silanol condensation catalyst relative to 100 parts by mass of a base resin, and grafting the grafting reaction site with a site capable of undergoing a grafting reaction of the base resin by radicals generated from the organic peroxide, thereby obtaining a silane crosslinkable resin composition containing a silane crosslinkable resin. Step (2): A step of molding the silane-crosslinkable resin composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked resin molded product. The base resin has a density of 0.890 g / cm 3 and a glass transition temperature of -50°C or less, 10 to 50 mass% of a polyolefin resin, and a density of 0.890 g / cm 3 The composition comprises 3 to 10 mass % of a polyolefin resin having a glass transition temperature of more than -50°C and not more than -40°C, a styrene elastomer, and a mineral oil, The blending amount of the inorganic filler is 0.5 parts by mass or more relative to 100 parts by mass of the base resin, the amount of the component having a melting point of 250° C. or more is 15.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition; In carrying out the step (1), A method for producing a silane-crosslinked resin molded product, wherein in the case where the entire base resin is melt-mixed in the following step (a), step (1) comprises the following steps (a) and (c), and in the case where only a part of the base resin is melt-mixed in the following step (a), step (1) comprises the following steps (a), (b) and (c). Step (a): A step of melt-mixing all or a part of the base resin, the inorganic filler, and the silane coupling agent in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and grafting the graft reaction site with a graftable site of the base resin by radicals generated from the organic peroxide to prepare a silane master batch containing a silane crosslinkable resin. step (b): melt mixing the remainder of the base resin and the silanol condensation catalyst to prepare a catalyst master batch; and Step (c): A step of melt-mixing the silane master batch and the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable resin composition. [2] The method for producing a silane-crosslinked resin molded product according to [1], wherein the amount of the component having a melting point of 250°C or higher is 10.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition. [3] The method for producing a silane-crosslinked resin molded article according to [1] or [2], wherein the base resin contains 10 to 50% by mass of the styrene elastomer and 10 to 50% by mass of the mineral oil. [4] The base resin has a density of 0.890 g / cm 3 The method for producing a silane-crosslinked resin molded product according to any one of [1] to [3], comprising: 10 to 30 mass % of a polyolefin resin having a glass transition temperature of -50°C or lower, 20 to 50 mass % of the styrene elastomer, and 20 to 50 mass % of the mineral oil. [5] The method for producing a silane-crosslinked resin molded article according to any one of [1] to [4], wherein the inorganic filler is a metal hydrate, calcium carbonate, silica, antimony trioxide, or a mixture thereof. [6] A method for producing a silane-crosslinkable resin composition, comprising the following step (1): Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base resin, and a silanol condensation catalyst relative to 100 parts by mass of a base resin, and grafting the grafting reaction site with a site capable of undergoing a grafting reaction of the base resin by radicals generated from the organic peroxide, thereby obtaining a silane crosslinkable resin composition containing a silane crosslinkable resin. The base resin has a density of 0.890 g / cm 3 and a glass transition temperature of -50°C or less, 10 to 50 mass% of a polyolefin resin, and a density of 0.890 g / cm 3 The composition comprises 3 to 10 mass % of a polyolefin resin having a glass transition temperature of more than -50°C and not more than -40°C, a styrene elastomer, and a mineral oil, The blending amount of the inorganic filler is 0.5 parts by mass or more relative to 100 parts by mass of the base resin, the amount of the component having a melting point of 250° C. or more is 15.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition; In carrying out the step (1), A method for producing a silane-crosslinkable resin composition, wherein in the case where the whole of the base resin is melt-mixed in the following step (a), step (1) comprises the following steps (a) and (c), and in the case where only a part of the base resin is melt-mixed in the following step (a), step (1) comprises the following steps (a), (b) and (c). Step (a): A step of melt-mixing all or a part of the base resin, the inorganic filler, and the silane coupling agent in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and grafting the graft reaction site with a graftable site of the base resin by radicals generated from the organic peroxide to prepare a silane master batch containing a silane crosslinkable resin. step (b): melt mixing the remainder of the base resin and the silanol condensation catalyst to prepare a catalyst master batch; and Step (c): A step of melt-mixing the silane master batch and the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable resin composition. [7] A silane-crosslinkable resin composition produced by the production method according to [6]. [8] A silane-crosslinked resin molded article produced by the method according to any one of [1] to [5]. [9] A product comprising the silane-crosslinked resin molded article according to [8].
[10] The product according to [9], wherein the silane crosslinked resin molded body is provided as a coating for an insulated electric wire or an optical fiber cable.
[0009] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. Effect of the Invention
[0010] According to the present invention, there can be provided a method for producing a silane-crosslinked resin molded article having excellent low-temperature flexibility in an extremely low-temperature environment and excellent handleability at room temperature, a silane-crosslinked resin molded article obtained by this production method, and a product using this molded article. In addition, there can be provided a silane-crosslinkable resin composition suitable for producing a silane-crosslinked resin molded article having such excellent properties, and a production method thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present invention, an extremely low temperature is any temperature below −40° C., and refers to, for example, a temperature in the vicinity of −60° C. (−65 to −55° C.). In the present invention, normal temperature refers to a temperature of 15 to 25°C. First, each component used in the present invention will be described.
[0012] <Base resin> The base resin used in the present invention has a density of 0.890 g / cm as a resin component. 3 and a polyolefin resin with a glass transition temperature of -50°C or less and a density of 0.890g / cm 3 The composition contains a polyolefin resin having a glass transition temperature of more than -50°C and not more than -40°C, a styrene elastomer, and a mineral oil. Each of these components has a site capable of undergoing a graft reaction with the graft reaction site of the silane coupling agent in the presence of radicals generated from an organic peroxide, such as an unsaturated bond site of a carbon chain or a carbon atom having a hydrogen atom in the main chain or at its terminal.
[0013] - Polyolefin resin - Density 0.890g / cm 3 and a glass transition temperature of -50°C or less (PO-A); and 3 and a glass transition temperature of more than -50°C and -40°C or less (PO-B). The density of PO-A is 0.890 g / cm 3 Less than 0.860-0.880g / cm 3 is preferable, and 0.860 to 0.870 g / cm 3 If the density is too high, excellent low-temperature flexibility may not be achieved. The density of PO-B is 0.890g / cm 3 Less than 0.865-0.885g / cm 3 is preferable, and 0.875 to 0.885 g / cm 3 is more preferred. The density of polyolefin resin refers to the density (mass per unit volume) at a temperature of 20°C measured in accordance with JIS K 0061:2001 (Method of measuring density and specific gravity of chemical products). The glass transition temperature of PO-A is −50° C. or lower, preferably −55° C. or lower, and more preferably −60° C. or lower. There is no particular lower limit, but a temperature of about −75° C. is practical. The glass transition temperature of PO-B is more than -50°C and not more than -40°C, preferably from -45 to -40°C, and more preferably from -43 to -40°C. Glass transition temperature of PO-A (Tg A ) and the glass transition temperature (Tg B ) and (Tg B -Tg A ) is preferably 5 to 15°C, and more preferably 10 to 15°C. In the present invention, the glass transition temperature of the polyolefin resin refers to the glass transition temperature measured by DSC (differential scanning calorimeter). The glass transition temperature was measured by heating at 5° C. / min, cooling, and then heating again at 5° C. / min. PO-A and PO-B can be selected from polyolefin resins described below that have the above-mentioned density and glass transition temperature. In the present invention, when the term "polyolefin resin" is used without specifying the density and glass transition temperature, it means that the density and glass transition temperature are not limited. PO-A is preferably a polyethylene resin and an ethylene rubber. PO-B is preferably a polyethylene resin.
[0014] The polyolefin resin is not particularly limited as long as it is a resin made of a polymer obtained by polymerizing or copolymerizing a compound having an ethylenically unsaturated bond (usually an alkene). Conventionally known polyolefin resins used in insulated wires and cables can be used. Examples of polyolefin resins include resins made of polymers such as polyethylene, polypropylene, ethylene-α-olefin copolymers, polyolefin copolymers having an acid copolymer component or an acid ester copolymer component, and rubbers or elastomers of these polymers (excluding styrene elastomers). Examples of rubbers include ethylene rubber. The polyolefin resins may be used alone or in combination of two or more kinds. The polyolefin resin may be acid-modified with a commonly used unsaturated carboxylic acid or a derivative thereof.
[0015] Examples of the polyethylene resin include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and very low-density polyethylene (VLDPE). Of these, linear low-density polyethylene and low-density polyethylene are preferred.
[0016] The polypropylene resin includes not only propylene homopolymers, but also ethylene-propylene copolymers such as random polypropylene and block polypropylene resins as copolymers.
[0017] The ethylene-α-olefin copolymer resin is preferably a resin of a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms (excluding those corresponding to the above-mentioned polyethylene and polypropylene).
[0018] Examples of resins made of polyolefin copolymers having an acid copolymerization component or an acid ester copolymerization component include resins made of ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-alkyl(meth)acrylate copolymers (preferably those having an alkyl group having 1 to 12 carbon atoms), etc. Among these, ethylene-alkyl(meth)acrylate copolymers are preferred.
[0019] The ethylene rubber is not particularly limited as long as it is a rubber of a copolymer of ethylene and an α-olefin. For example, the ethylene rubber may be a binary copolymer rubber of ethylene and an α-olefin (preferably an α-olefin having 1 to 12 carbon atoms), or a ternary copolymer rubber of ethylene, an α-olefin (preferably an α-olefin having 1 to 12 carbon atoms), and a third component having an unsaturated bond other than an α-olefin. The third component may be a conjugated or non-conjugated diene, specifically, butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, dicyclopentadiene (DCPD), ethylidene norbornene (ENB), 1,4-hexadiene, etc. The binary copolymer rubber may be ethylene-propylene rubber (EPM), and the ternary copolymer rubber may be ethylene-propylene-diene rubber (EPDM).
[0020] - Styrene elastomer - The styrene elastomer used in the present invention is a copolymer block of components derived from an aromatic vinyl compound and a conjugated diene compound, and / or a hydrogenated product of a block copolymer or random copolymer mainly composed of components derived from the above compounds. The aromatic vinyl compound may be one or more selected from, for example, styrene, α-methylstyrene, vinyltoluene, p-tertiary butylstyrene, etc., with styrene being preferred among them. The conjugated diene compound may be one or more selected from, for example, butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, etc., with butadiene, isoprene, or a combination thereof being preferred among them. As the styrene elastomer, a binary or ternary copolymer composed of a polystyrene block and an elastomer block having a polyolefin structure can be used. The hydrogenated copolymer (hereinafter sometimes referred to as hydrogenated copolymer) preferably contains 5 to 70 mass %, more preferably 10 to 60 mass %, of a component derived from an aromatic vinyl compound. This content can be determined, for example, by measuring the UV absorption spectrum with an ultraviolet spectrophotometer using a chloroform solution. Examples of styrene elastomers include SBS (styrene-butadiene-styrene block copolymer), SIS (styrene-isoprene-styrene block copolymer), SEBS (styrene-ethylene-butylene-styrene block copolymer: hydrogenated SBS), SEEPS (styrene-ethylene-ethylene-propylene-styrene block copolymer), SEPS (styrene-ethylene-propylene-styrene block copolymer: hydrogenated SIS), HSBR (hydrogenated styrene-butadiene random copolymer), etc. The styrene elastomer may be one type or two or more types. Examples of styrene elastomers include "Septon" (product name, manufactured by Kuraray Co., Ltd.), "Tuftec" (product name, manufactured by Asahi Kasei Chemicals Corporation), and "Dynaron" (product name, manufactured by JSR Corporation).
[0021] - Mineral oil - The mineral oil used in the present invention is a mixed oil containing an oil having an aromatic ring, an oil having a naphthene ring, and an oil having a paraffin chain. Paraffin oil refers to an oil in which the carbon number (CP) of the paraffin chain is, for example, 50% or more and less than 75% of the total carbon number of the aromatic ring, naphthene ring, and paraffin chain, the carbon number (CN) of the naphthene chain is 20 or more and less than 40%, and the carbon number of the aromatic ring (CA) is 3 or more and less than 10%. Naphthene oil refers to an oil in which CN is 40 or more and less than 60%, CP is 30% or more and less than 50%, and CA is 8% or more and less than 16% of the total carbon number, and aromatic oil refers to an oil in which CA is 16% or more. As the mineral oil (rubber softener), paraffin oil or naphthene oil can be used, with paraffin oil being preferred in terms of mechanical strength. The paraffin oil preferably has a dynamic viscosity at 40°C of 20 to 500 cSt, a pour point of -10 to -15°C, and a flash point (COC) of 180 to 300°C. Examples of mineral oils include "Diana Process Oil" (trade name, manufactured by Idemitsu Kosan Co., Ltd.) and "Cosmo Neutral" (trade name, manufactured by Cosmo Oil Lubricants Co., Ltd.).
[0022] - Other base resin components - Resins or rubbers other than those mentioned above may be used as long as the effects of the present invention are not impaired.
[0023] - Content in base resin - The content of each component in the base resin is determined within the following range so that the total of each component is 100% by mass. The base resin contains 10 to 50% by mass of PO-A, 3 to 10% by mass of PO-B, a styrene elastomer, and a mineral oil.
[0024] The content of PO-A is 10 to 50% by mass in 100% by mass of the base resin. Within this range, sufficient low-temperature flexibility can be achieved. The content of PO-A is preferably 10 to 30% by mass, and more preferably 10 to 20% by mass. The PO-B content is 3 to 10% by mass in 100% by mass of the base resin. Within this range, low-temperature flexibility and room temperature handleability can be improved. The PO-B content is preferably 5 to 10% by mass, and more preferably 5 to 7% by mass. The content of the styrene elastomer is not particularly limited, but is preferably from 7 to 50 mass%, more preferably from 10 to 50 mass%, more preferably from 20 to 50 mass%, and particularly preferably from 20 to 35 mass%, based on 100 mass% of the base resin. The content of the mineral oil is not particularly limited, but is preferably 7 to 50 mass %, more preferably 10 to 50 mass %, more preferably 20 to 50 mass %, and particularly preferably 30 to 40 mass %, based on 100 mass % of the base resin. The base resin preferably contains 10 to 50% by mass of a styrene elastomer and 10 to 50% by mass of a mineral oil. The base resin preferably contains 10 to 30% by mass of PO-A, 20 to 50% by mass of styrene elastomer, and 20 to 50% by mass of mineral oil.
[0025] <Organic peroxide> The organic peroxide generates radicals at least by thermal decomposition, and acts as a catalyst to initiate a grafting reaction of the silane coupling agent to the resin component by radical reaction (a covalent bond forming reaction between the grafting reaction site of the silane coupling agent and the grafting reaction site of the resin component, also called a (radical) addition reaction). In particular, when the silane coupling agent contains an ethylenically unsaturated group as the grafting reaction site, the organic peroxide acts to initiate a grafting reaction by radical reaction between the ethylenically unsaturated group and the resin component (including a reaction of abstracting hydrogen radicals from the resin component). The organic peroxide is not particularly limited as long as it generates radicals. For example, an organic peroxide represented by the general formula: 1 -O-O-R 2 , R 3 -OO-C(=O)R 4 , R 5 C(=O)-OO(C=O)R 6 Preferred are compounds represented by the formula: 1 ~R 6 Each independently represents an alkyl group, an aryl group, or an acyl group. R 1 ~R 6 Among these, it is preferable that all of them are alkyl groups, or that one of them is an alkyl group and the remaining is an acyl group.
[0026] Examples of such organic peroxides include those described in paragraph
[0037] of International Publication No. 2015 / 046478, the contents of which are incorporated herein by reference as part of the present specification. In terms of odor, coloring, and scorch stability, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3 are preferred.
[0027] The decomposition temperature of the organic peroxide is preferably 120 to 195° C., particularly preferably 125 to 180° C. The decomposition temperature of the organic peroxide is equal to or lower than the melt mixing temperature in the step (a) described below. In the present invention, the decomposition temperature of an organic peroxide means the temperature at which a single-component organic peroxide undergoes a decomposition reaction into two or more compounds when heated at a certain temperature or temperature range. Specifically, it means the temperature at which heat absorption or heat generation begins when heated from room temperature at a temperature increase rate of 5°C / min in a nitrogen gas atmosphere by thermal analysis such as DSC method.
[0028] <Inorganic filler> In the present invention, the inorganic filler can be used without any particular limitation as long as it has a site on its surface that can form a hydrogen bond or the like with a reactive site such as a silanol group of a silane coupling agent, or a site that can be chemically bonded by a covalent bond. Examples of the site in the inorganic filler that can be chemically bonded with a reactive site of a silane coupling agent include OH groups (hydroxyl groups, water molecules of water of water or crystallization, OH groups such as carboxyl groups), amino groups, and SH groups.
[0029] Examples of inorganic fillers that can be used include metal hydrates such as aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whiskers, hydrated aluminum silicate, hydrated magnesium silicate, basic magnesium carbonate, and compounds having hydroxyl groups or crystal water, such as hydrotalcite, boron nitride, silica (crystalline silica, amorphous silica, etc.), carbon black, clay, zinc oxide, tin oxide, titanium oxide, molybdenum oxide, antimony trioxide, silicone compounds, quartz, talc, zinc borate, white carbon, zinc borate, zinc hydroxystannate, and zinc stannate. One type of inorganic filler may be used alone, or two or more types may be used in combination.
[0030] The melting point of the inorganic filler is not particularly limited, but is preferably 250° C. or higher. In this case, the amount of the inorganic filler is included in the "amount of components having a melting point of 250° C. or higher" described later. The average particle size of the inorganic filler is preferably 0.2 to 10 μm, more preferably 0.3 to 8 μm, further preferably 0.4 to 5 μm, and particularly preferably 0.4 to 3 μm. The average particle size is determined by dispersing the inorganic filler in alcohol or water and using an optical particle size measuring device such as a laser diffraction / scattering type particle size distribution measuring device.
[0031] The inorganic filler may be surface-treated with a silane coupling agent or the like. For example, silane coupling agent surface-treated metal hydrates include Kisuma 5L and Kisuma 5P (both trade names, magnesium hydroxide, manufactured by Kyowa Chemical Industry Co., Ltd., etc.). The amount of the silane coupling agent used to surface-treat the inorganic filler is not particularly limited, but is, for example, 3 mass% or less.
[0032] It is preferable to use an inorganic filler having a high density. In this way, it is possible to improve low-temperature flexibility while ensuring the amount of inorganic filler required for silane grafting. The density of the inorganic filler is not particularly limited, but is preferably 3.0 g / cm.3 More than 3.2 g / cm is preferable. 3 The upper limit of the density of the inorganic filler is not particularly limited, but is preferably 6.0 g / cm 3 The following is practical.
[0033] Of these, the inorganic filler is preferably a metal hydrate (more preferably magnesium hydroxide), silica, antimony trioxide, or a mixture thereof.
[0034] <Organic flame retardants> As the organic flame retardant, organic flame retardants used in cables and wiring materials can be used without any particular limitation. The organic flame retardant is preferably a halogen-based flame retardant (bromine-based flame retardant), a phosphorus-based flame retardant, a nitrogen-based flame retardant, etc., and more preferably a bromine-based flame retardant. The organic flame retardant is not particularly limited, but is preferably an organic flame retardant having a melting point of 250°C or higher. When the melting point of the organic flame retardant is 250°C or higher, the amount of the organic flame retardant is also included in the "amount of components having a melting point of 250°C or higher" described below.
[0035] <Silane coupling agent> The silane coupling agent used in the present invention has a grafting reaction site (group or atom) that can undergo grafting reaction with base resin in the presence of radicals generated by decomposition of organic peroxide. It also has a reaction site (hydrolyzable silyl group) that can react with the site that can chemically bond with inorganic filler and undergo silanol condensation. Examples of such silane coupling agents include silane coupling agents used in conventional silane crosslinking methods. Examples of the silane coupling agent include silane coupling agents having an unsaturated group, and specifically include vinyl alkoxy silanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tributoxy silane, vinyl dimethoxy ethoxy silane, vinyl dimethoxy butoxy silane, vinyl diethoxy butoxy silane, allyl trimethoxy silane, allyl triethoxy silane, and vinyl triacetoxy silane, and (meth) acryloxy alkoxy silanes such as methacryloxy propyl triethoxy silane and methacryloxy propyl methyl dimethoxy silane. Among them, vinyl trimethoxy silane or vinyl triethoxy silane is particularly preferred. The silane coupling agent may be used alone or in combination of two or more. The silane coupling agent may be used as it is, or may be used after being diluted with a solvent.
[0036] <Silanol condensation catalyst> The silanol condensation catalyst functions to cause a condensation reaction of the silane coupling agent grafted to the base resin in the presence of moisture, and the resin components are crosslinked together via the silane coupling agent based on the function of the silanol condensation catalyst. Such silanol condensation catalysts are not particularly limited, and examples thereof include organotin compounds, metal soaps, platinum compounds, etc. Examples of organotin compounds include dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctiate, dibutyltin diacetate, and other organotin compounds. The silanol condensation catalyst may be used alone or in combination of two or more.
[0037] <Additives> In the present invention, various additives that are generally used in insulated wires, electric cables, electric cords, automotive parts, office automation equipment, building parts, miscellaneous goods, sheets, foams, tubes, and pipes may be appropriately blended within a range that does not impair the intended effects. Examples of such additives include crosslinking assistants, antioxidants, lubricants, metal deactivators, flame retardants (assistants), and other resins.
[0038] The crosslinking aid is a compound that forms a partially crosslinked structure with a resin component in the presence of an organic peroxide, and examples of such compounds include polyfunctional compounds. The antioxidant is not particularly limited, but examples thereof include amine antioxidants, phenol antioxidants, and sulfur antioxidants. Examples of the lubricant include hydrocarbons, siloxanes (including silicone gums), fatty acids, fatty acid amides, esters, alcohols, metal soaps, etc. As the lubricant, silicone gums are preferred.
[0039] <Components with a melting point of 250°C or higher> The silane crosslinkable resin composition preferably contains a component having a melting point of 250° C. or higher among the above components. Examples of components having a melting point of 250° C. or higher include components (compounds) other than the above resins that have a melting point of 250° C. or higher, and specifically refer to components that can exist in a solid state (particles, powder) during melt mixing when preparing the silane crosslinkable resin composition (the components themselves do not change, specifically, do not melt, decompose (thermal decomposition), or change in quality (removal of hydration water, etc.)). Examples of such components are not particularly limited, and include, for example, the above inorganic fillers, organic flame retardants, etc. In the present invention, the melting point is a value measured in an ordinary pressure (1 atm) environment according to the method specified in JIS K 0064.
[0040] <Method of manufacturing silane crosslinked resin molded body> The method for producing a silane-crosslinked resin molded article of the present invention will now be described in detail. The method for producing a silane-crosslinked resin molded article of the present invention includes the following steps (1), (2), and (3). The silane-crosslinkable resin composition of the present invention is produced by the following step (1).
[0041] Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base resin, and a silanol condensation catalyst relative to 100 parts by mass of a base resin, and grafting the grafting reaction site with the grafting reaction site of the base resin by radicals generated from the organic peroxide, thereby obtaining a silane crosslinkable resin composition containing a silane crosslinkable resin. Step (2): A step of molding the silane-crosslinkable resin composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked resin molded product.
[0042] The above step (1) includes the following steps depending on the use mode of the base resin. When the entire base resin is melt-mixed in the following step (a), step (1) has the following steps (a) and (c), and when a portion of the base resin is melt-mixed in the following step (a), step (1) has the following steps (a), (b) and (c). Step (a): A step of preparing a silane master batch containing a silane crosslinkable resin by melt-mixing all or a part of a base resin, an inorganic filler, and a silane coupling agent in the presence of an organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and grafting a graft reaction site with a graftable site of the base resin by radicals generated from the organic peroxide. Step (b): melt mixing the remainder of the base resin and a silanol condensation catalyst to prepare a catalyst masterbatch; and Step (c): A step of melt-mixing the silane master batch with a silanol condensation catalyst or a catalyst master batch to obtain a silane crosslinkable resin composition.
[0043] In the manufacturing method of the present invention, the "base resin" is a resin for forming a silane crosslinked resin molded product or a silane crosslinkable resin composition. Therefore, in the manufacturing method of the present invention, it is sufficient that the reaction composition obtained in step (1) contains 100 parts by mass of the base resin. For example, in step (a), the embodiment includes "an embodiment in which the entire amount (100 parts by mass) of the base resin is blended" and "an embodiment in which a part of the base resin is blended." When a part of the base resin is blended in step (a), the blending amount of 100 parts by mass of the base resin in step (1) is the total amount of the base resin melt-mixed in step (a) and step (b).
[0044] In step (1), when a portion of the base resin is blended in step (a) and the remainder of the base resin is blended in step (b), preferably 70 to 95 mass %, more preferably 75 to 92 mass %, of the base resin is blended in step (a), and preferably 5 to 30 mass %, more preferably 8 to 25 mass %, of the base resin is blended in step (b).
[0045] In the step (1), the blending amounts (contents) of PO-A, PO-B, the styrene elastomer and the mineral oil in the base resin are as described above. The base resin components blended in step (a) are not particularly limited, but it is preferable to blend PO-A, PO-B, a styrene elastomer, and a mineral oil, and it is more preferable to blend PO-A, a styrene elastomer, and a mineral oil. The base resin component to be blended in step (b) is not particularly limited, but it is preferable to blend PO-A, PO-B, a styrene elastomer, and a mineral oil.
[0046] In step (1), the amount of the organic peroxide is 0.01 to 0.5 parts by mass, preferably 0.01 to 0.4 parts by mass, and more preferably 0.05 to 0.2 parts by mass, relative to 100 parts by mass of the base resin. By setting the amount of the organic peroxide to 0.01 to 0.5 parts by mass, the grafting reaction can be carried out in an appropriate range, and condensation between silane coupling agents can be suppressed. In addition, direct crosslinking of the resin components due to side reactions can be suppressed.
[0047] In step (1), the blending amount (mass basis) of the inorganic filler is 0.5 parts by mass or more relative to 100 parts by mass of the base resin, preferably 3 to 100 parts by mass, more preferably 5 to 50 parts by mass, relative to 100 parts by mass of the base resin. Furthermore, among the components constituting the silane crosslinkable resin composition, the blending amount (volume basis) of the component having a melting point of 250° C. or more (hereinafter also referred to as high melting point component) is 15.0 volume % or less based on the total volume of the components constituting the silane crosslinkable resin composition. By blending the high melting point component in the above amount, it is possible to realize low temperature flexibility while properly carrying out the grafting reaction. The amount of the high melting point component (by volume) is preferably 10.0% by volume or less, more preferably 7.0% by volume or less, based on the total volume of the components constituting the silane crosslinkable resin composition. The lower limit is not particularly limited, but 0.1% by volume or more is practical. In the present invention, the amount (by volume) of the high melting point component relative to the total volume of the components constituting the silane crosslinkable resin composition can be determined from the amount and density of each component. The density of each component constituting the silane crosslinkable resin composition refers to the density at 20°C measured according to JIS K 0061:2001 (Method of measuring density and specific gravity of chemical products). Specifically, the density of organic substances (base resin components other than mineral oil and lubricants) that are solid at the above temperature can be determined by the balance method in 8.1 of the above JIS. The density of organic substances (mineral oil, silane coupling agent, organic peroxide, and silanol condensation catalyst) that are liquid at the above temperature can be determined by the hydrometer method in 7.1 of the above JIS. The density of inorganic substances (inorganic filler and antioxidant) that are solid at the above temperature can be determined by the pycnometer method in 8.2 of the above JIS. However, the density of organic flame retardants with a melting point of 250°C or higher among the organic flame retardants is determined by the pycnometer method. The density of components other than these can be measured by selecting an appropriate method of the above JIS. The above density is calculated to three decimal places for the polyolefin resin and mineral oil among the base resin components, and for the organic peroxide, and to two decimal places for components other than these. The volume (Vf) of the high melting point component can be obtained by multiplying the reciprocal of the density obtained above by the amount of the high melting point component per 100 parts by mass of the base resin. When multiple types of high melting point components are used, the volume of each is calculated separately, and the total volume is the volume of the high melting point component. The total volume (Vtotal) of the components constituting the silane crosslinkable resin composition can be obtained by multiplying the inverse of the density of each component obtained above by the amount of each component per 100 parts by mass of the base resin, and adding up the resulting values. When multiple types of components of the same category are used, the volume of each component is calculated separately. For each resin component constituting the base resin, the volume is calculated by taking the content of each component in 100 parts by mass of the base resin as the amount of each resin component per 100 parts by mass of the base resin. The amount of the high-melting point component (by volume) is calculated by calculating the ratio (Vf / Vtotal × 100) of the volume of the high-melting point component (Vf) determined as described above to the total volume (Vtotal) of the components constituting the silane-crosslinkable resin composition, to one decimal place. The above can be summarized as follows. Amount of high melting point component (by volume) = Volume of high melting point component (Vf) / Total volume of components constituting the silane crosslinkable resin composition (V total ) x 100 Volume of high melting point component (Vf) = reciprocal of density of high melting point component × amount of high melting point component blended per 100 parts by mass of base resin (parts by mass) The total volume (V total ) = reciprocal of density of component A × amount of component A blended per 100 parts by mass of base resin (parts by mass) + Inverse of density of component B × amount of component B blended per 100 parts by mass of base resin (parts by mass) ... + reciprocal of density of component X × amount of component X blended per 100 parts by mass of base resin (parts by mass) Here, components A to X are components that constitute the silane crosslinkable resin composition.
[0048] In step (1), the amount of the silane coupling agent is 1 to 15 parts by mass, preferably 1.5 to 7 parts by mass, and more preferably 2 to 5 parts by mass, based on 100 parts by mass of the base resin. When the amount of the silane coupling agent is 1 to 15 parts by mass, the silane coupling agent is adsorbed on the surface of the inorganic filler, and the silane coupling agent is prevented from volatilizing during kneading, which is economical. Furthermore, the crosslinking reaction can be sufficiently promoted.
[0049] In step (1), the amount of the silanol condensation catalyst is not particularly limited, and is preferably 0.01 to 0.5 parts by mass, more preferably 0.02 to 0.5 parts by mass, still more preferably 0.05 to 0.4 parts by mass, and particularly preferably 0.08 to 0.3 parts by mass, relative to 100 parts by mass of the base resin. When the amount of the silanol condensation catalyst is within the above range, crosslinking proceeds sufficiently.
[0050] The silane master batch can be prepared by melt-kneading all or a part of the base resin, the inorganic filler, and the silane coupling agent in the above-mentioned amounts at a temperature equal to or higher than the decomposition temperature of the organic peroxide, thereby inducing the above-mentioned grafting reaction. In the present invention, "melt-mixing all or a part of the base resin, the inorganic filler, and the silane coupling agent" does not mean that the order of mixing is specified when melt-mixing, and the mixing may be performed in any order. That is, the order of mixing in step (a) is not particularly limited. The method of mixing the base resin is not particularly limited. For example, a base resin that has been mixed and prepared in advance may be used, or each component, for example, each resin component may be mixed separately.
[0051] In the present invention, it is preferable to premix (pre-mix) the inorganic filler with the silane coupling agent. That is, in the present invention, it is preferable to (melt) mix the above-mentioned components in the following steps (a-1) and (a-2). Step (a-1): A step of mixing an inorganic filler and a silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture with all or a part of the base resin at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause a graft reaction between the graft reaction site and the graft reaction site of the base resin by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable resin.
[0052] The above step (a-2) includes an embodiment in which the entire amount (100 parts by mass) of the base resin is blended, and an embodiment in which only a portion of the base resin is blended. When a portion of the base resin is blended in step (a-2), the remainder of the base resin is blended in step (b). When a portion of the base resin is blended in step (a-2), 100 parts by mass of the base resin blended in steps (a) and (b) is the total amount of the base resin mixed in steps (a-2) and (b).
[0053] In step (a-1), the method of premixing the inorganic filler and the silane coupling agent is not particularly limited, and includes mixing methods such as wet processing, dry processing, etc. Specifically, the method includes a method of mixing the inorganic filler and the silane coupling agent by dry or wet processing for several minutes to several hours at a temperature below the decomposition temperature of the organic peroxide, preferably 10 to 60°C, more preferably around room temperature (20 to 25°C), and more preferably a dry processing in which the silane coupling agent is added to the inorganic filler, preferably the dried inorganic filler, with or without heating and mixed. The premixed silane coupling agent is present so as to surround the surface of the inorganic filler, and it is considered that a part or the whole of the silane coupling agent is adsorbed or bonded to the inorganic filler, which reduces the volatilization of the silane coupling agent during the melt mixing in the subsequent step (a-2). In step (a-1), a base resin may be mixed as long as the temperature is maintained below the decomposition temperature.
[0054] Next, the mixture of inorganic filler and silane coupling agent obtained in step (a-1) and all or part of the base resin are melt-mixed while being heated to a temperature equal to or higher than the decomposition temperature of the organic peroxide in the presence of the organic peroxide (step (a-2)). In this way, excessive crosslinking reaction between the base resin components can be prevented, and a crosslinked molded product with excellent appearance can be obtained. In the melt mixing step (a-2), the radicals generated from the organic peroxide cause a graft reaction between the graft reaction site of the silane coupling agent and the graft reaction site of the base resin. As a result, a silane crosslinkable resin (silane graft polymer) in which the silane coupling agent is covalently bonded to the resin component is synthesized, and a silane master batch containing this silane crosslinkable resin is prepared.
[0055] In step (a-2), the temperature at which the above components are melt-mixed (also referred to as melt-kneading or kneading) is equal to or higher than the decomposition temperature of the organic peroxide, preferably a temperature of the decomposition temperature of the organic peroxide + (25 to 110) ° C, more preferably 150 to 230 ° C. The decomposition temperature of the organic peroxide is preferably set after the base resin component is melted. At the above mixing temperature, the above components melt, the organic peroxide decomposes and acts, and the necessary silane grafting reaction proceeds sufficiently in step (a-2). The mixing time may be a time at which the reaction mixture is sufficiently mixed and the silane grafting reaction can be completed, and is appropriately set between 3 and 40 minutes, but is not limited thereto. Other conditions can be appropriately set. The mixing method is not particularly limited as long as it is a method commonly used for resins, plastics, etc. As a kneading device, a single screw extruder, a twin screw extruder, a roll, a Banbury mixer, various kneaders, etc. are used. In terms of dispersibility of the base resin component and stability of the crosslinking reaction, a closed type mixer such as a Banbury mixer or various kneaders is preferred.
[0056] The high melting point components other than the organic peroxide and the inorganic filler may be present during the melt mixing in the above step (a-2), that is, when the mixture obtained in step (a-1) is melt mixed with the base resin. The high melting point components other than the organic peroxide and the inorganic filler may be mixed, for example, in step (a-1) or in step (a-2). The high melting point components other than the organic peroxide and the inorganic filler are preferably mixed in step (a-1).
[0057] In the present invention, when the above-mentioned components are melt-mixed at once (step (a)), the conditions for melt-mixing are not particularly limited, but the conditions for the above-mentioned step (a-2) can be adopted. In this case, a part or the whole of the silane coupling agent is adsorbed or bonded to the inorganic filler during melt mixing.
[0058] In steps (a), (a-1) and (a-2), especially in step (a-2), it is preferable to knead the above-mentioned components substantially without mixing the silanol condensation catalyst. This can suppress the condensation reaction of the silane coupling agent, facilitate melt mixing, and obtain the desired shape during extrusion molding. Here, "substantially without mixing" does not mean to exclude the silanol condensation catalyst that is inevitably present, but means that it may be present to the extent that the above-mentioned problems due to the silanol condensation of the silane coupling agent do not occur. For example, in step (a-2), the silanol condensation catalyst may be present in an amount of 0.01 parts by mass or less relative to 100 parts by mass of the base resin.
[0059] In this manner, step (a) (preferably step (a) consisting of the above steps (a-1) and (a-2)) is carried out to graft react the silane coupling agent with the base resin to prepare a silane master batch (also called silane MB). The silane MB thus obtained is used, as described below, in the production of the reaction composition (silane crosslinkable resin composition) prepared in step (1), preferably together with a silanol condensation catalyst or a catalyst master batch described below. Silane MB is a mixture containing a silane crosslinkable resin in which the silane coupling agent has been graft-reacted to a resin component to an extent that it can be molded in step (2) described below.
[0060] In the manufacturing method of the present invention, when a part of the base resin is melt-mixed in step (a), the remaining part of the base resin is melt-mixed with a silanol condensation catalyst to prepare a catalyst master batch (also called catalyst MB) in step (b). Therefore, when the whole of the base resin is melt-mixed in step (a), step (b) does not need to be performed, and the silanol condensation catalyst may be mixed with another base resin component.
[0061] The mixing ratio of the base resin as the carrier and the silanol condensation catalyst is not particularly limited, but is preferably set so as to satisfy the above blending amounts in step (1). The mixing may be performed by any method that can achieve uniform mixing, including mixing performed under molten base resin (melt mixing). Melt mixing can be performed in the same manner as in the melt mixing in the above step (a-2). For example, the mixing temperature can be appropriately set to a temperature equal to or higher than the melting temperature of the base resin component, and is preferably 120 to 200°C, more preferably 140 to 180°C. Other conditions, such as the mixing time, can be appropriately set.
[0062] In step (b), other resins can be used as carriers instead of or in addition to the remainder of the base resin. That is, in step (b), the remainder of the base resin when a part of the base resin is melt-mixed in step (a), or a resin other than the resin component used in step (a), can be melt-mixed with a silanol condensation catalyst to prepare a catalyst master batch. When the carrier is another resin, the amount of the other resin is preferably 1 to 60 parts by mass, more preferably 2 to 50 parts by mass, and even more preferably 3 to 40 parts by mass, relative to 100 parts by mass of the base resin, in order to promote the grafting reaction in step (a) and to prevent the formation of bumps during molding.
[0063] In addition, in step (b), an inorganic filler can be mixed in. In this case, the amount of the inorganic filler in step (b) is not particularly limited and is appropriately set in consideration of the above-mentioned amount of the inorganic filler, and can be, for example, 10 parts by mass or less.
[0064] The catalyst MB thus prepared is a (molten) mixture of the silanol condensation catalyst and the carrier, with or without a filler. This catalyst MB is used together with the silane MB in the production of the silane crosslinkable resin composition prepared in step (1).
[0065] In the manufacturing method of the present invention, the next step is to melt-mix the silane MB with the silanol condensation catalyst or catalyst MB to obtain a silane crosslinkable resin composition (reaction composition). This reaction composition is a composition containing the silane crosslinkable resin synthesized in the above step (a) (step (a-2)). The mixing method may be any method capable of obtaining a homogeneous reaction composition as described above.
[0066] The mixing is basically the same as the melt mixing in step (a). Although there are resin components, such as elastomers, whose melting points cannot be measured by DSC or the like, the kneading is carried out at a temperature at which at least the resin components melt. The melting temperature is appropriately selected according to the melting temperature of the base resin or carrier, and is, for example, preferably 80 to 250°C, more preferably 100 to 240°C. Other conditions, such as the mixing (kneading) time, can be appropriately set.
[0067] In step (c), in order to avoid silanol condensation reactions, it is preferable that the mixture of silane MB and silanol condensation catalyst is not kept at high temperature for a long period of time.
[0068] This step (c) may be any step in which the silane master batch and the silanol condensation catalyst are mixed to obtain the above-mentioned reaction composition as a molten mixture thereof, and is preferably a step in which the catalyst master batch containing the silanol condensation catalyst and the carrier is melt-mixed with the silane master batch.
[0069] In this way, steps (a) to (c) (step (1)) are carried out to produce a silane crosslinkable resin composition as a reaction composition. This silane crosslinkable resin composition contains 10 to 50 mass % of PO-A, 3 to 10 mass % of PO-B, a styrene elastomer, a silane crosslinkable resin in which a silane coupling agent is grafted onto a base resin containing a mineral oil, and a silanol condensation catalyst per 100 mass parts of the base resin, the content of the inorganic filler is 0.5 mass parts or more per 100 mass parts of the base resin, and the amount of the high melting point component is 15.0 volume % or less with respect to the total volume of the components constituting the silane crosslinkable resin composition. This silane crosslinkable resin composition contains a silane crosslinkable resin with a different crosslinking method. In this silane crosslinkable resin, the reactive site of the silane coupling agent capable of silanol condensation may be bonded or adsorbed to an inorganic filler, but is not silanol condensed as described below. Therefore, the silane crosslinkable resin includes at least a crosslinkable resin in which a silane coupling agent bonded or adsorbed to an inorganic filler is grafted to a base resin, and a crosslinkable resin in which a silane coupling agent not bonded or adsorbed to an inorganic filler is grafted to a base resin. In addition, the silane crosslinkable resin may have a silane coupling agent bonded or adsorbed to an inorganic filler, and a silane coupling agent not bonded or adsorbed to an inorganic filler. Furthermore, it may contain a resin component that has not reacted with the silane coupling agent. As described above, the silane crosslinkable resin is an uncrosslinked body in which the silane coupling agent is not condensed with silanol. In practice, when melt-mixed in step (c), partial crosslinking is unavoidable, but the obtained silane crosslinkable resin composition is one that maintains at least the moldability in the molding in step (2).
[0070] In step (1), steps (a) to (c) can be carried out simultaneously or consecutively.
[0071] In step (1), the amounts of other base resin components and the above-mentioned additives that can be used in addition to the above-mentioned components are appropriately set within ranges that do not impair the object of the present invention. In step (1), the additives, particularly the antioxidants, may be mixed in any step or component, but are preferably mixed in the carrier. In step (1), particularly in step (a), it is preferable that the crosslinking aid is not substantially mixed. If the crosslinking aid is not substantially mixed, crosslinking between the resin components during melt mixing is difficult to occur. Here, "not substantially mixed" means that the crosslinking aid is not actively mixed, and does not exclude unavoidable mixing.
[0072] In the method for producing a silane-crosslinked resin molded article of the present invention, steps (2) and (3) are then carried out. In the method for producing a silane-crosslinked resin molded product of the present invention, a step (2) is carried out in which the obtained reaction composition is molded to obtain a molded product. This step (2) is sufficient as long as it can mold the reaction composition, and the molding method and molding conditions are appropriately selected depending on the form of the silane-crosslinked resin molded product of the present invention or the silane-crosslinked resin molded product containing the silane-crosslinked resin molded product. Examples of the molding method include extrusion molding using an extruder, extrusion molding using an injection molding machine, and molding using other molding machines. Extrusion molding is preferred when the silane-crosslinked resin molded product of the present invention or the silane-crosslinked resin molded product containing the silane-crosslinked resin molded product is an insulated electric wire or an optical fiber cable. When step (2) is carried out by extrusion molding, the molding speed (extrusion speed) is not particularly limited, and can usually be set to a linear speed of 10 to less than 250 m / min, preferably 20 to 100 m / min.
[0073] In addition, step (2) can be carried out simultaneously with or consecutively to step (c). That is, as one embodiment of the melt mixing in step (c), the molding raw materials can be melt mixed during melt molding, for example, during extrusion molding, or immediately before that. For example, pellets such as dry blends can be mixed together at room temperature or high temperature and introduced into a molding machine (melt mixing), or they can be melt mixed after mixing, pelletized again, and introduced into a molding machine. More specifically, a series of steps can be adopted in which a molding material consisting of silane MB and silanol condensation catalyst or catalyst MB is melt-kneaded in a coating device, and then extrusion-coated on the outer peripheral surface of a conductor or the like, and molded into a desired shape. In this way, a molded article of the silane crosslinkable resin composition is obtained. Although partial crosslinking is inevitable for this molded article, as with the silane crosslinkable resin composition, it is in a partially crosslinked state that retains moldability that allows it to be molded in step (2). Therefore, the silane crosslinked resin molded article of this invention is made into a crosslinked or final crosslinked molded article by carrying out step (3).
[0074] In the method for producing a silane-crosslinked resin molded article of the present invention, a step (3) is carried out in which the molded article obtained in the step (2) is brought into contact with water. As a result, the reactive sites of the silane coupling agent capable of silanol condensation are hydrolyzed to silanol groups, and the hydroxyl groups of the silanol groups are condensed with each other by the silanol condensation catalyst present in the molded article to cause a crosslinking reaction. In this way, a silane-crosslinked resin molded article in which the silane coupling agent is crosslinked by silanol condensation can be obtained. The treatment in step (3) itself can be carried out by a normal method. Condensation between silane coupling agents proceeds simply by storing at room temperature, for example, 20 to 25°C. Therefore, in step (3), it is not necessary to actively bring the molded body into contact with water. In order to promote this crosslinking reaction, the molded body can also be actively brought into contact with moisture. For example, a method of actively bringing the molded body into contact with water, such as immersion in warm water, immersion in a moist heat bath, or exposure to high-temperature water vapor, can be adopted. In addition, pressure may be applied at this time to allow moisture to penetrate into the interior.
[0075] In this way, a silane crosslinked resin molded body is produced from the silane crosslinkable resin composition of the present invention. As described below, this silane crosslinked resin molded body contains a crosslinked resin in which the silane crosslinkable resin is condensed through a siloxane bond. One embodiment of this silane crosslinked resin molded body contains a silane crosslinked resin and an inorganic filler. Here, the inorganic filler may be bonded to the silane coupling agent of the silane crosslinked resin. Therefore, this silane crosslinked resin contains at least a crosslinked resin in which a plurality of crosslinked resins are bonded or adsorbed to the inorganic filler by the silane coupling agent, and bonded (crosslinked) through the inorganic filler and the silane coupling agent, and a crosslinked resin in which the reactive sites of the silane coupling agent of the crosslinkable resin are hydrolyzed and undergo a silanol condensation reaction with each other, and thus crosslinked through the silane coupling agent. In addition, the silane crosslinked resin may be a mixture of bonds (crosslinks) through the inorganic filler and the silane coupling agent and crosslinks through the silane coupling agent. Furthermore, it may contain a resin component unreacted with the silane coupling agent and / or a silane crosslinkable resin that is not crosslinked.
[0076] Although the details of how the production method of the present invention enables the realization of excellent properties in a silane-crosslinked resin molded article are not yet clear, it is believed to be as follows. According to the manufacturing method of the present invention, in step (a), a base resin, an inorganic filler, and a silane coupling agent are melt-mixed at a temperature equal to or higher than the decomposition temperature of the organic peroxide, thereby causing a grafting reaction. In step (3), the silane crosslinkable resin obtained by this grafting reaction is brought into contact with moisture to form a crosslinked resin having a crosslinked structure via a silanol bond. In the present invention, by blending an inorganic filler in step (a), a bond via the inorganic filler is also formed. In the manufacturing method of the present invention, the formation of a crosslinked structure by the above-mentioned silane crosslinking is assumed, and then, as the base resin, PO-A having a glass transition temperature of -50°C or less, PO-B having a glass transition temperature of -40 to -50°C, a styrene elastomer, a mineral oil, and an inorganic filler are used in specific amounts together with other components. Here, among the components of the base resin, PO-A mainly contributes to low-temperature flexibility, and PO-B mainly contributes to suppression of tackiness. In the present invention, by blending these PO-A and PO-B in an appropriate ratio together with other components, it is possible to achieve both flexibility at -60°C and handleability at room temperature. In particular, blending PO-B leads to reducing tackiness while maintaining low-temperature flexibility. In order to achieve both of the above properties, the amounts of inorganic filler and high-melting point component are also important. By setting the amount of inorganic filler to 0.5 parts by mass or more relative to the base resin and setting the amount of high-melting point component to 15 volume % or less, it is possible to achieve the above-mentioned low-temperature flexibility while ensuring the amount of inorganic filler necessary to form silane crosslinks.
[0077] The manufacturing method of the present invention can be applied to the manufacture of products (including semi-finished products, parts, and members) that require low-temperature flexibility, products that require crosslinking in addition to low-temperature flexibility, and components or members of products such as resin materials. Therefore, a silane-crosslinked resin molded product or a product containing a silane-crosslinked resin molded product is considered to be such a product. Examples of such products include coating materials for insulated wires such as flame-retardant insulated wires or flame-retardant cables, materials for wires and cables that are substitutes for rubber, and other flame-retardant wire parts, flame-retardant heat-resistant sheets, and flame-retardant films. Other examples include power plugs, connectors, sleeves, boxes, tape substrates, tubes, sheets, packings, cushioning materials, vibration-proof materials, wiring materials used for internal wiring and external wiring of electric and electronic devices, insulated wires, cables, cords, optical fiber cores, and optical fiber cords.
[0078] The manufacturing method of the present invention is particularly suitable for the manufacture of insulated electric wires and optical fiber cables, among the products that require low-temperature flexibility, and can form the coatings (insulators, sheaths) thereof.
[0079] When the silane crosslinked resin molded product of the present invention or the product containing the silane crosslinked resin molded product is an extrusion molded product such as an insulated electric wire or cable, it can be produced by, for example, preparing a silane crosslinkable resin composition by melt-kneading the molding material in an extruder (extrusion coating device) and carrying out the above-mentioned grafting reaction, and extruding the silane crosslinkable resin composition around the outer periphery of a conductor or the like to coat the conductor or the like (step (c) and step (2)). The temperature of the extrusion molding device at this time is preferably about 120 to 180 ° C. in the cylinder part and about 160 to 210 ° C. in the crosshead part, depending on the various conditions such as the type of resin and the take-up speed of the conductor or the like. The silane crosslinked resin molded product or the silane crosslinked resin molded product containing the silane crosslinked resin molded product can be molded by extrusion coating the silane crosslinkable resin composition to which a large amount of inorganic filler has been added, around the conductor, or around the conductor to which tensile strength fibers are attached or twisted, using a general-purpose extrusion coating device without using a special machine such as an electron beam crosslinker. For example, the conductor is preferably a metal conductor, and a single wire or a twisted wire of soft copper, copper alloy, aluminum, etc. can be used. In addition to bare wire, a conductor that is tin-plated or has an enamel-coated insulating layer can also be used. The thickness of the insulating layer (coating layer made of the silane-crosslinkable resin composition of the present invention) formed around the conductor is not particularly limited, but is usually about 0.15 to 5 mm. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. In Tables 1-1 and 1-2 (collectively referred to as Table 1), the numerical values for the blending amounts of each example are in parts by mass unless otherwise specified. Furthermore, blank spaces for each component mean that the blending amount of the corresponding component is 0 parts by mass.
[0081] In Examples 1 to 16 and Comparative Examples 1 to 10, a part of the components constituting the base resin was used as a carrier resin for the catalyst MB.
[0082] (Examples 1 to 16, Comparative Examples 1 to 10) First, the inorganic filler, the silane coupling agent, the organic peroxide, and the bromine-based flame retardant were charged in a rotary blade mixer (product name, Mazera PM, manufactured by Mazera Co., Ltd.) in the mass ratio shown in Table 1, and stirred (premixed) at room temperature (25 ° C.) and 10 rpm for 1 minute to obtain a powder mixture (step (a-1)). Next, the obtained powder mixture, the base resin, and the lubricant were charged in a kneader (volume 75 L) previously heated to 100 ° C. in the mass ratio shown in Table 1, mixed at 40 rpm for 5 minutes, and then finished kneaded at 30 rpm for 3 minutes. However, in Example 8, the above-mentioned premixing step was not performed, and the raw materials were directly charged into the kneader. After confirming that the temperature of the mixture reached 180 to 200 ° C., which is the decomposition temperature of the organic peroxide or higher, the mixture was pelletized using a feeder-ruder and a pelletizer to obtain a silane master batch (step (a-2)). The Silane MB thus obtained contains a silane crosslinkable resin in which a silane coupling agent has been grafted to a resin component.
[0083] On the other hand, the base resin, inorganic filler, antioxidant and silanol condensation catalyst were sequentially charged in the mass ratios shown in Table 1 into a kneader (volume 75 L) that had been preheated to 80°C, mixed at 30 rpm for 5 minutes, and then finish-kneaded at 25 rpm for 3 minutes. After it was confirmed that the temperature of the mixture had reached about 160°C and the base resin had been sufficiently melted and mixed, the mixture was pelletized using a feeder-ruder and pelletizer to obtain a catalyst master batch (step (b)). This catalyst MB is a molten mixture of the carrier resin and the silanol condensation catalyst.
[0084] Next, the silane MB and catalyst MB were charged into a closed ribbon blender and dry-blended for 5 minutes at room temperature (25° C.) to obtain a dry blend. At this time, the mixing ratio of the silane MB and catalyst MB was the mass ratio shown in Table 1.
[0085] The dry blend was then melt mixed and molded under either of the following molding conditions (1) or (2) to obtain a coated conductor or an uncrosslinked sheet, respectively (step (c) and step (2)). The dry blend was melt mixed in a molding machine before molding (step (c)) to prepare a silane crosslinkable resin composition as a reaction composition. This silane crosslinkable resin composition is a melt mixture of silane MB and catalyst MB, and contains the above-mentioned silane crosslinkable resin.
[0086] (Molding condition 1: Extrusion molding) An extruder equipped with a screw having a screw diameter of 40 mm and L / D (ratio of effective screw length L to diameter D) = 24 was set to a compression screw temperature of 160°C and a head temperature of 180°C. The prepared dry blend was charged into the extruder and melt mixed (step (c)), and extruded and coated to a thickness of 1 mm on the outside of a 1 / 0.8A conductor made of bare soft copper wire to obtain a coated conductor having an outer diameter of 2.8 mm (step (2)). The obtained coated conductor was left to stand for 24 hours in an atmosphere of 60°C and 95% RH to promote silane crosslinking (step (3)). In this way, each insulated electric wire was produced in which the conductor was coated with a silane crosslinked resin molded body. The silane crosslinked resin molded body as the coating contains the above-mentioned silane crosslinked resin.
[0087] (Molding condition 2: Sheet molding) The prepared dry blend was melt-mixed for 10 minutes using an 8-inch roll heated to 180°C (step (c)), and formed into a sheet to obtain a strip-shaped sheet having a thickness of about 2.1 mm (step (2)). This strip-shaped sheet was then cut into A4 size sheets and pressed at 180°C for 10 minutes using an 80t press machine to obtain an uncrosslinked sheet having a thickness of 2 mm. The uncrosslinked sheet obtained was allowed to stand for 24 hours in an atmosphere of 60°C and 95% RH to allow silane crosslinking to proceed (step (3)). In this manner, a sheet made of a silane crosslinked resin molded product was produced. The obtained sheet of the silane crosslinked resin molded product contains the above-mentioned silane crosslinked resin.
[0088] The components shown in Table 1 were as follows. (1) Polyolefin resin 1: Engage 7387 (trade name, manufactured by Dow, LLDPE, glass transition temperature -52°C, density 0.870 g / cm 3 ) (2) Polyolefin resin 2: Engage 8150 (trade name, manufactured by Dow, LLDPE, glass transition temperature -52°C, density 0.868g / cm 3 ) (3) Polyolefin resin 3: EPT3092PM (product name, manufactured by Mitsui Chemicals, Inc., EPDM, glass transition temperature -53°C, density 0.870 g / cm 3 ) (4) Polyolefin resin 4: Evolu SP0540 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, glass transition temperature -70°C, density 0.905g / cm 3 ) (5) Polyolefin resin 5: Engage 7256 (trade name, manufactured by Dow, LLDPE, glass transition temperature -42°C, density 0.885g / cm 3 ) (6) Styrene elastomer 1: Septon 4077 (trade name, manufactured by Asahi Kasei Corporation, SEEPS, density 0.91 g / cm 3 ) (7) Styrene elastomer 2: Tuftec N504 (product name, manufactured by Asahi Kasei Corporation, SEPS, density 0.91 g / cm 3 ) (8) Mineral oil 1: Cosmo Neutral 500 (product name, manufactured by Cosmo Oil Lubricants Co., Ltd., density 0.885 g / cm 3 ) (9) Brominated flame retardant 1: SAYTEX 8010 (product name, manufactured by Albemarle, brominated flame retardant, density 3.25 g / cm 3 , melting point 345℃) (10) Inorganic filler 1: PATOX-C (product name, manufactured by Nippon Seiko Co., Ltd., antimony trioxide, density 5.40 g / cm 3 , melting point 656℃) (11) Inorganic filler 2: Magseeds FK-640 (product name, manufactured by Konoshima Chemical Co., Ltd., magnesium hydroxide, density 2.38 g / cm 3 , decomposition temperature: 300℃ or higher) (12) Inorganic filler 3: Boehmite FKB-104 (product name, manufactured by Konoshima Chemical Co., Ltd., aluminum hydroxide, density 3.00 g / cm 3 , decomposition temperature: 500℃ or higher) (13) Inorganic filler 4: Crystallite 5X (trade name, manufactured by Tatsumori Co., Ltd., crystalline silica, density 2.60 g / cm 3 , melting point 1710℃) (14) Inorganic filler 5: AEROSIL 200 (product name, manufactured by Nippon Aerosil Co., Ltd., dry silica, density 2.20 g / cm 3 , melting point 1700℃) (15) Inorganic filler 6: Softon 1200 (product name, manufactured by Bihoku Powder Industry Co., Ltd., calcium carbonate, density 2.70 g / cm 3 , decomposition temperature: 825℃) (16) Lubricant 1: X-21-3043 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., silicone gum, density 0.98 g / cm 3 ) (17) Silane coupling agent 1: KBM-1003 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., vinyltrimethoxysilane, density 0.97 g / cm 3 , melting point 0℃) (18) Organic peroxide 1: Perhexa 25B (trade name, NOF Corporation, dicumyl peroxide, density 0.873 g / cm 3 , melting point 3.9℃) (19) Antioxidant 1: Irganox 1076 (trade name, manufactured by BASF, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, density 1.02 g / cm 3 , melting point 55℃) (20) Silanol condensation catalyst 1: Adeka STAB OT-1 (trade name, manufactured by ADEKA Corporation, dioctyltin dilaurate, density 1.00 g / cm 3 , melting point 7.5℃)
[0089] The density of each of the above components (1) to (20) was measured in accordance with JIS K 0061:2001. The densities of (1) to (7) and (16) were measured using the balance method in JIS 8.1, those of (8), (17), (18) and (20) were measured using the hydrometer method in JIS 7.1, and those of (9) to (15) and (19) were measured using the pycnometer method in JIS 8.2. Table 1 shows the density of each component measured as above. Using the density thus obtained and the amount of the high melting point component per 100 parts by mass of the base resin shown in the table, the ratio of the volume of the high melting point component to the total volume of the components constituting the silane crosslinkable resin composition was calculated.
[0090] The insulated wire and sheet thus obtained were evaluated for various properties by the test methods shown below.
[0091] <Cryogenic flexibility test> Using the insulated wires manufactured as described above, the flexibility at -60°C was evaluated according to a method in accordance with JIS C 3005 (2014) (4.20 Low-temperature winding, Method A). The insulated wire and mandrels with diameters of 2.8 mm (same diameter as the outer diameter of the insulated wire) and 5.6 mm (twice the outer diameter of the insulated wire) were placed in a cryogenic chamber at -60°C and cooled for at least one hour. After that, in the cryogenic chamber, the insulated wire was wound around the 2.8 mm mandrel and the 5.6 mm mandrel, each for 6 turns, and the wire was checked for whether it could be wound and the surface condition of the insulated wire after winding, and evaluated according to the following criteria. A wire that can be wound around a 2.8 mm diameter mandrel with no gaps between the insulated wire and the mandrel and that does not develop cracks on the surface of the insulated wire after winding is rated as "A" for excellent low-temperature flexibility. The insulated wire can be wound six times around a 2.8 mm diameter mandrel, although there is a gap between the insulated wire and the mandrel, and can be wound around a 5.6 mm diameter mandrel without any gap between the insulated wire and the mandrel. In either case, the insulated wire shows no cracks on the surface after winding. This is considered to have excellent low-temperature flexibility (B). A wire that can be wound six turns around a 5.6 mm diameter mandrel, even if a gap occurs between the insulated wire and the mandrel, and that does not develop cracks on the surface of the insulated wire after winding, is rated as having good low-temperature flexibility "C". The wires that could not be wound six turns around any of the mandrels, or the wires that had visible cracks on the surface after being wound around any of the mandrels, were rated as having poor low-temperature flexibility "D". Here, "a gap is generated" means that the maximum distance between the surface of the mandrel and the surface of the insulated wire is 1 to 2 mm, and "the wire cannot be wound" means that the maximum distance exceeds 2 mm. The passing level for this exam is a grade of "C" or above.
[0092] <Tackiness test> In order to evaluate the handling property at room temperature, a tackiness test was carried out using the sheet produced above. The tackiness was evaluated using the adhesiveness between the sheets as an index. The produced sheet was cut into 5 cm squares at room temperature (23°C) and 50% RH, and two of the resulting 2 mm thick, 5 cm square sheets were placed on a horizontal table with one on top of the other, and a load of 5 kg was applied so that pressure was applied uniformly from above. After leaving the sheet to stand for 30 minutes at room temperature (23°C) and 50% RH, the load was removed and the adhesion between the sheets was measured. The sheets are not bonded together, or are partially bonded together, but when one of the sheets is picked up by the edge and lifted up at the non-bonded portion, it can be peeled off by its own weight alone. "A" is a sheet with little tackiness and excellent properties. "B" is a sheet with little tack and good adhesion; "C" is a sheet with little tack and good adhesion; "D" is a sheet with little tack and good adhesion; "E" is a sheet with little tack and good adhesion; "F" is a sheet with little tack and good adhesion; "G" is a sheet with little tack and good adhesion; "H .... Sheets that were strongly bonded to each other and that were deformed when the two sheets were held at the same edge and peeled off, and did not retain their 5 cm square shape after peeling, were rated as "D" as having significant tackiness and failing the test. Here, "not maintaining the shape of a 5 cm square" refers to a state in which, when the sheet is observed immediately after deformation, the entire sheet does not fit within an area of 5.5 cm square. The passing level for this exam is a grade of "B" or above. If the above evaluation is rated "B" or higher, for example, when a wiring material is coated with a silane crosslinked resin molded product, even if the coatings are brought into contact with each other, the wiring material can be peeled off at the contact point without deforming the wiring material.
[0093] <Heat deformation test> In order to evaluate whether the molded article was sufficiently crosslinked, a heat deformation test was carried out using the produced insulated wire. The heat deformation test was performed based on JIS C 3005:2014 (4.23 Heat deformation) at a measurement temperature of 120°C and a load of 5 N. The heat deformation rate (reduction rate) was calculated from the thickness of the coating after heating and the thickness before heating. A heat deformation rate of 20% or less was rated as extremely excellent ("A"), a deformation rate of more than 20% but less than 30% was rated as excellent ("B"), a deformation rate of more than 30% but less than 40% was rated as good ("C"), and a deformation rate of more than 40% was rated as failing ("D"). A rating of "C" or higher is the pass level for this test.
[0094] [Table 1-1]
[0095] [Table 1-2]
[0096] When a high melting point component was mixed in an excessively large amount into the manufacturing method having the respective steps specified in the present invention, the product failed the cryogenic flexibility test, and it was not possible to produce a silane crosslinked resin molded product that had both low-temperature flexibility in a cryogenic environment and handleability at room temperature (Comparative Examples 1 and 2). When an inorganic filler was not used in the manufacturing method having the respective steps specified in the present invention, the product failed the heat distortion test, and it was not possible to produce a silane crosslinked resin molded product in which crosslinking was formed to the degree normally required for crosslinked polyethylene insulated electric wires (Comparative Example 3). When a base resin that does not satisfy the composition specified in the present invention was mixed into the manufacturing method having the respective steps specified in the present invention, the product failed any of the cryogenic flexibility test, the tackiness test, and the heat distortion test, and it was not possible to produce a silane crosslinked resin molded product that had both low-temperature flexibility in a cryogenic environment and handleability at room temperature (Comparative Examples 4, 5, 8 to 10). When an organic peroxide is mixed in an amount that is too large or too small for the manufacturing method having each step specified in the present invention, the product fails any of the cryogenic flexibility test, tackiness test, and heat deformation test, and not only could a silane crosslinkable molded product that had both low-temperature flexibility in a cryogenic environment and handleability at room temperature be produced, but also could not be produced with sufficient crosslinking (Comparative Examples 6 and 7). Note that the manufacturing method of Comparative Example 10 produced a silane crosslinkable resin molded product that passed the same cryogenic flexibility test as the above-mentioned cryogenic flexibility test, except that the test temperature was -40°C. In contrast, in a manufacturing method having each step specified in the present invention, when a base resin satisfying the composition specified in the present invention is mixed with a high melting point component containing an inorganic filler, an organic peroxide, etc. in a specific amount, it is possible to manufacture a silane crosslinked resin molded article that passes both the cryogenic flexibility test and the tackiness test and has both low temperature flexibility in a cryogenic environment and handleability at room temperature (Examples 1 to 16). Furthermore, since it passes the heat deformation test, it is understood that a molded article having a degree of crosslinking normally required for wiring materials for the above-mentioned applications has been manufactured.
Claims
1. A method for producing a silane-crosslinked resin molded product, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base resin, and a silanol condensation catalyst relative to 100 parts by mass of a base resin, and grafting the grafting reaction site with a site capable of undergoing a grafting reaction of the base resin by radicals generated from the organic peroxide to obtain a silane crosslinkable resin composition containing a silane crosslinkable resin. Step (2): A step of molding the silane-crosslinkable resin composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a silane-crosslinked resin molded product. The base resin has a density of 0.890 g / cm 3 and a glass transition temperature of -50°C or less, 10 to 50 mass% of a polyolefin resin, and a density of 0.890 g / cm 3 The composition contains 3 to 10 mass % of a polyolefin resin having a glass transition temperature of more than -50°C and not more than -40°C, a styrene elastomer, and a mineral oil, The blending amount of the inorganic filler is 0.5 parts by mass or more relative to 100 parts by mass of the base resin, the amount of the component having a melting point of 250° C. or more is 15.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition; In carrying out the step (1), A method for producing a silane-crosslinked resin molded product, wherein in the case where the entire base resin is melt-mixed in the following step (a), step (1) has the following steps (a) and (c), and in the case where only a part of the base resin is melt-mixed in the following step (a), step (1) has the following steps (a), (b) and (c). Step (a): A step of melt-mixing all or a part of the base resin, the inorganic filler, and the silane coupling agent in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and grafting the graft reaction site with a graftable site of the base resin by radicals generated from the organic peroxide to prepare a silane master batch containing a silane crosslinkable resin. Step (b): melt-mixing the remainder of the base resin and the silanol condensation catalyst to prepare a catalyst master batch; and Step (c): A step of melt-mixing the silane master batch and the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable resin composition.
2. 2. The method for producing a silane-crosslinked resin molded article according to claim 1, wherein the amount of the component having a melting point of 250° C. or higher is 10.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition.
3. 3. The method for producing a silane-crosslinked resin molded article according to claim 1, wherein the base resin contains 10 to 50% by mass of the styrene elastomer and 10 to 50% by mass of the mineral oil.
4. The base resin has a density of 0.890 g / cm 3 The method for producing a silane-crosslinked resin molded article according to any one of claims 1 to 3, comprising: 10 to 30 mass% of a polyolefin resin having a glass transition temperature of -50°C or less; 20 to 50 mass% of the styrene elastomer; and 20 to 50 mass% of the mineral oil.
5. The method for producing a silane-crosslinked resin molded article according to any one of claims 1 to 4, wherein the inorganic filler is a metal hydrate, calcium carbonate, silica, antimony trioxide, or a mixture thereof.
6. A method for producing a silane-crosslinkable resin composition, comprising the following step (1): Step (1): A step of melt-mixing 0.01 to 0.5 parts by mass of an organic peroxide, an inorganic filler, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base resin, and a silanol condensation catalyst relative to 100 parts by mass of a base resin, and grafting the grafting reaction site with a site capable of undergoing a grafting reaction of the base resin by radicals generated from the organic peroxide to obtain a silane crosslinkable resin composition containing a silane crosslinkable resin. The base resin has a density of 0.890 g / cm 3 and a glass transition temperature of -50°C or less, 10 to 50 mass% of a polyolefin resin, and a density of 0.890 g / cm 3 The composition contains 3 to 10 mass % of a polyolefin resin having a glass transition temperature of more than -50°C and not more than -40°C, a styrene elastomer, and a mineral oil, The blending amount of the inorganic filler is 0.5 parts by mass or more relative to 100 parts by mass of the base resin, the amount of the component having a melting point of 250° C. or more is 15.0% by volume or less based on the total volume of the components constituting the silane-crosslinkable resin composition; In carrying out the step (1), A method for producing a silane-crosslinkable resin composition, wherein in the case where the whole of the base resin is melt-mixed in the following step (a), the step (1) has the following steps (a) and (c), and in the case where only a part of the base resin is melt-mixed in the following step (a), the step (1) has the following steps (a), (b) and (c). Step (a): A step of melt-mixing all or a part of the base resin, the inorganic filler, and the silane coupling agent in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and grafting the graft reaction site with a graftable site of the base resin by radicals generated from the organic peroxide to prepare a silane master batch containing a silane crosslinkable resin. Step (b): melt-mixing the remainder of the base resin and the silanol condensation catalyst to prepare a catalyst master batch; and Step (c): A step of melt-mixing the silane master batch and the silanol condensation catalyst or the catalyst master batch to obtain the silane crosslinkable resin composition.
7. A silane-crosslinkable resin composition produced by the process according to claim 6.
8. A silane-crosslinked resin molded article produced by the method according to any one of claims 1 to 5.
9. A product comprising the silane-crosslinked resin molded article according to claim 8.
10. The product according to claim 9 , wherein the silane-crosslinked resin molded article is provided as a coating for an insulated electric wire or an optical fiber cable.
Citation Information
Patent Citations
Crosslinked resin molded body, crosslinkable resin composition and manufacturing method of them, silane masterbatch and molded article
JP2016074853A
Electric wire-coating material composition, insulated wire, and wire harness
JP2017174551A
Fire retardant crosslinked resin molded body, fire retardant crosslinkable resin composition and manufacturing method therefor, fire retardant silane master batch and fire retardant molded article
JP2017179235A
cable
JP2018195575A
High flexible electric wire and cable for in-wheel motor
JP2019008888A